Determining the nutritional value and antioxidant capacity of duckweed (Wolffia arrhiza) under artificial conditions. (January 2022) - Hu, Zhubin; Fang, Yang; Yi, Zhuolin; Tian, Xueping; Li, Jinmeng; Jin, Yanling; He, Kaize; Liu, Penghui; Du, Anping; Huang, Yuhong; Zhao, Hai
Abstract: Duckweeds are traditionally used as a plant protein source in some Southeast Asian countries. In this study, we first obtained a high-protein strain ( Wolffia arrhiza 7678a) under artificial conditions and determined its protein content in 50.89% of dry weight. More importantly, we further investigated its nutritional properties. The digestible indispensable amino acids score (DIAAS) reached 0.75, indicating the good protein quality of W. arrhiza . The proportion of unsaturated fatty acids in total fatty acids (TFA) was 70.85%, and three main fatty acids (palmitic acid, linoleic acid, α-linolenic acid) accounted for 89.7% of TFA. Compared with the conventional crops, it had much higher contents of total phenolics and flavonoids and showed higher antioxidant activities. Also, the low concentrations of antinutritional factors could make the nutrients of W. arrhiza easily absorbed. Therefore, W. arrhiza showed a great potential value for human food. Highlights: Protein content of W. arrhiza was more than 50% of the dry weight. Digestible indispensable amino acid score indicated its good protein quality. High contents of phenolics and flavonoids hinted its great antioxidant activity. Antinutritional factors in W. arrhiza were much lower than the common crops.